Analisis Pengelolaan Surat Masuk dan Surat Keluar di Southeast Asian Ministers Of Education Organizational Regional Centre For Food and Nutrition (Seameo Recfon) - Tantri Nurpratiwi; Christian Wiradendi Wolor; Adnan Kasofi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the management of incoming and outgoing mail at SEAMEO RECFON. The research method used is descriptive analysis with a qualitative approach, which involves describing and analyzing the problems identified. The study is based on both primary and secondary data. Primary data were obtained through observation, interviews, and documentation, while secondary data were gathered from books, previous research, and relevant articles. The data analysis technique used follows the interactive model of Miles and Huberman, which includes four stages: data collection, data reduction, data display, and conclusion drawing/verification. The sampling technique employed is purposive sampling. The results show that the management of incoming and outgoing mail has been carried out in a structured manner using a combination of manual and digital methods. However, several challenges remain, including limited human resources, technical issues with the e-paraf and e-sign systems, and a lack of compliance with administrative standards. To address these challenges, SEAMEO RECFON has implemented staff training, internal evaluations, SOP development, and strengthened activity planning. These efforts reflect the organization’s commitment to building a modern and adaptive correspondence management system.